2018
DOI: 10.1021/acsaem.8b01414
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of SnS and SnS2 Nanosheets for FTO/SnS/SnS2/Pt Photocathode

Abstract: Two-dimensional (2D) materials have attracted great attention recently. SnS/SnS 2 with sheet-like morphologies are widely used in photoelectric devices because of their excellent electronic transportation properties. In our study, by changing the mole ratios of SnCl 2 and C 2 H 5 NS at reaction temperatures as high as 280−300 °C, SnS rectangular nanosheets are converted successfully to SnS 2 hexagonal nanosheets with a one-pot method. SEM, XRD, Raman, and XPS analyses were utilized to examine the physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…However, the energy does not correspond to the band gap of SnS around 825 nm (1.5 eV) and the large peak width is not characteristic of a single and well-dened energy transition. 61 A report on 2D akes of SnS 2 synthesized by a wet chemical synthesis technique, shows similar features on the PL spectrum (at 532 nm) with a sharp peak at about 580 nm (indirect excitonic peak as previously assigned) and a broader peak centered at about 660 nm. 11 The authors associated this transition to indirect exciton recombination of 4H phase of SnS 2 present in the sample, rejecting the other possibilities due to the high quality of their synthetized SnS 2 akes (no impurities, no sulfur vacancies, etc.).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…However, the energy does not correspond to the band gap of SnS around 825 nm (1.5 eV) and the large peak width is not characteristic of a single and well-dened energy transition. 61 A report on 2D akes of SnS 2 synthesized by a wet chemical synthesis technique, shows similar features on the PL spectrum (at 532 nm) with a sharp peak at about 580 nm (indirect excitonic peak as previously assigned) and a broader peak centered at about 660 nm. 11 The authors associated this transition to indirect exciton recombination of 4H phase of SnS 2 present in the sample, rejecting the other possibilities due to the high quality of their synthetized SnS 2 akes (no impurities, no sulfur vacancies, etc.).…”
Section: Resultssupporting
confidence: 65%
“…10b) is composed of a one doublet, with S 2p 3/2 and S 2p 1/2 signal centered at 161.8 and 162.7 eV respectively, attributed to S 2À species in SnS 2 . 61 Both Sn 3d and S 2p conrms the successful formation of SnS 2 phase, without another phase. The Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While interface engineering by depositing n-type SnS 2 on the SnS surfaces allowed the formation of a p−n junction, this yielded a low photon-tocurrent conversion efficiency in the PEC device because of the small energy-level difference, i.e., the band gap at the junction interface (E g,int ) between the conduction-band minimum (CBM) of SnS and the valence-band maximum (VBM) of SnS 2 . 20 The small E g,int , which is lower than the carrier activation energy (∼0.76 eV) of SnS, likely acts as a Shockley− Read−Hall recombination site for holes from SnS and electrons from SnS 2 . 24,25 Because SnS has relatively high energy levels of the CBM and VBM compared with other ptype semiconductors, n-type materials having a small conduction-band offset with respect to SnS are needed to achieve a high E g,int p−n junction.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Sn-based chalcogenides composed of nontoxic and earth-abundant elements are promising candidates. , In particular, orthorhombic herzenbergite tin monosulfide (SnS) has an anisotropic two-dimensional (2D) layered orthorhombic crystal structure (space group: Pbnm ) in which in-plane covalent bonds are present, while van der Waals bonds exist vertically along the [010] direction. SnS has a suitable band gap (1.3 eV) for visible-light harvesting and exhibits a high hole mobility (∼90 cm 2 V –1 s –1 , ⊥ to the [010] axis), appropriate carrier concentrations (10 14 –10 17 cm –3 ), and a high optical absorption coefficient of 10 5 cm –1 in the visible region of the solar spectrum. The theoretical photocurrent density of −38 mA cm –2 can be achieved using orthorhombic SnS-based photocathodes, assuming a band gap of 1.3 eV and 100% incident photon-to-current conversion under simulated AM 1.5G solar irradiation. Despite these promising characteristics, the photocurrent density of SnS-based photocathodes reported to date is insufficient for application to real PEC devices. …”
Section: Introductionmentioning
confidence: 99%
“…55 Huang et al reported that the SnS x thin films changed from p-type to n-type when x = 1.15, as the increasing amount of Sn 4+ leads to n-type conductivity. 56 So it could be possible to form a homojunction with SnS x materials with a varied amount of S. Some groups actually have tried to fabricate SnS/SnS 2 devices, 57 but in general all SnS x materials coexist in a film and result in some detrimental effect in terms of performance. 58,59 Therefore, one important challenge in achieving high performance SnS-based solar energy conversion devices is to synthesize phase-pure SnS while suppressing the secondary phases, SnS 2 and Sn 2 S 3 .…”
Section: Emerging Binary Chalcogenides For Solarmentioning
confidence: 99%